Implementasi Dan Contoh Kasus Implementasi Hukum Pidana Di Indonesia - Muhammad Danial (Pusat Riset dan Inovasi Nasional, 2024)
Criminal law enforcement is an effort designed rationally to overcome crime by paying attention to the principles of justice and effectiveness. In its implementation, criminal law enforcement can also involve various aspects, such as drafting criminal legislation that is responsive to social and situational developments. This research aims to determine the value of implementation of criminal law in Indonesia. The method used is a normative legal research method carried out using analytical descriptive and normative juridical approaches. The implementation of criminal law in Indonesia involves a series of complex processes, starting from law enforcement to implementing sanctions. In this way, the implementation of criminal law in Indonesia involves a number of stages and aspects that reflect the state's efforts to create a legal system that is fair, transparent and in accordance with the values of justice and human rights.